2018
DOI: 10.1016/s2215-0366(18)30252-9
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride and olanzapine followed by open-label treatment with clozapine in first-episode schizophrenia and schizophreniform disorder (OPTiMiSE): a three-phase switching study

Abstract: European Commission Seventh Framework Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 24 publications
3
115
1
3
Order By: Relevance
“…This case report highlights the importance of clozapine for nonresponding patients in early stages of disease. Kahn et al [78] recently suggested that clozapine should be used after patients fail a single antipsychotic trial rather than after two different antipsychotics have been tried, as in the current recommendations. Clozapine may also exert a neuroprotective effect by restoring white matter integrity as described in our recently published study [79].…”
Section: Discussionmentioning
confidence: 99%
“…This case report highlights the importance of clozapine for nonresponding patients in early stages of disease. Kahn et al [78] recently suggested that clozapine should be used after patients fail a single antipsychotic trial rather than after two different antipsychotics have been tried, as in the current recommendations. Clozapine may also exert a neuroprotective effect by restoring white matter integrity as described in our recently published study [79].…”
Section: Discussionmentioning
confidence: 99%
“…non-clozapine) antipsychotic in the UK. It was decided that a stratifier would be more useful for patients who failed a first-line conventional antipsychotic than patients who are treatment-naïve, because the latter patient group has a high response rate to first-line conventional antipsychotic (ranges from 67.4 to 75.4% as reported by published literature [13,14]).…”
Section: Populationmentioning
confidence: 99%
“…There is a lack of clinical evidence about patients' response to a second-line antipsychotic after failing a first-line antipsychotic. According to a recent literature review [14], there are only two trials which examined patients' response to a second-line antipsychotic after failing a first-line antipsychotic: one is a naturalistic study conducted by Agid et al [13], and another is an openlabel treatment with clozapine in first-episode schizophrenia and schizophreniform disorder (OPTiMiSE) trial [14]. It was decided that the data reported by Agid et al is more appropriate for this model for two reasons: (1) Agid et al has a larger sample size than the OPTiMiSE trial (60 vs 39, number of patients who were switched to a second-line antipsychotic after failing a first-line antipsychotic); (2) The results of the OPTiMiSE trial indicated that for patients who did not achieve remission with a first-line antipsychotic within 4 weeks, switching to a second-line conventional antipsychotic did not improve their response rate-or in another word, for patients who failed a first-line antipsychotic, the proportion of AP2 responder is nearly zero.…”
Section: Input Datamentioning
confidence: 99%
See 1 more Smart Citation
“…While the current evidence is promising, well‐designed and well‐powered RCTs in patients with early‐phase schizophrenia will be needed to establish whether clozapine may indeed improve clinical outcome and quality of life. Indeed, a recent example of such a trial suggests that clozapine may have a role in a simple treatment algorithm for early‐stage schizophrenia .…”
mentioning
confidence: 99%